KEMISKINAN DAN LINGKUNGAN: PERSPEKTIF KEMISKINAN DI PERKOTAAN DAN PERDESAAN - Sedwivia Ridena (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2021)
The environment is an important part of sustainable development and is taken into account in all policies, programs, activities and decisions on funding and human welfare. Poverty is a multidimensional problem and is still the main focus of the government. Furthermore, poverty alleviation and environmental change are two important agendas in the sustainable development goals (SDGs). The study used panel data regression from 33 provinces in Indonesia except North Kalimantan Province (due to data limitations) and examined the relationship between poverty of the poor in urban and rural areas to the quality of the environment in 2013-2018. This study found that the urban poor and income inequality significantly reduce environmental quality. The poor who live in urban areas have more potential to damage the quality of the environment than the poor in rural areas. Likewise, a large inequality of income has a negative effect on the quality of the environment. The different perceptions of a good standard of living between the urban and rural poor may be the cause of the resulting differences in environmental quality.